Ação rescisória por violação a precedente - Santos, Welder Queiroz dos (2018)
This doctoral thesis has as its aim the study of the possibility of filing an action for the reversal of res judicata based on a brazilian precedent. The Brazilian Procedural Law Code (CPC) expressly provides the action for the reversal of res judicata based on a rule of law On the other hand, it created a list of binding precedents that are referred in this study as precedent, despite the numerous nicknames (or nomenclatures) verified in doctrine and jurisprudence. For this purpose, it analyses the function of the law to regulate as social relations and the principles of legal basis, equality and legal security. under its two perspectives: the subjective, decorrente da finalidade de garantir o estado ideal de previsibilidade de comportamento do Estado perante os atos dos cidadãos; e a objetiva, with the purpose of ensuring the stability of legal relations, protecting the perfect legal act, acquired right and res judicata. This paper analyses the concept, purpose, legal nature, object and hypothesis of the action for the reversal of res judicata. After, examine the meaning of the rule of law. At this time, examine the precedente as rule of law, the function of the precedente in common law and in civil law systems, the duty of standardization assigned to the Courts and to maintain the stability, consistency and integrity of case law and the duty to observe the precedents established by the Code of Civil Procedure. Finally, the thesis concluded for the possibility of filing an action for the reversal of res judicata based on a precedent and proposes solutions to complex questions regarding the moment of formation of the precedent, at the time of the final res judicata of the rescinded decision and action for the reversal of res judicata based on a precedent